Mitigasi Bencana Berbasis Kearifan Lokal oleh Masyarakat Kabupaten Pasaman - Ahmad, Taufani; Ekha Putera, Roni; Koeswara, Hendri (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This research aims to understand disaster mitigation based on local wisdom implemented by the community in Pasaman Regency. In this study, the researcher applies WN. Charter's disaster mitigation theory, which divides the concept of disaster mitigation into two parts: structural mitigation and non-structural mitigation. This research uses a qualitative descriptive method. Data collection techniques include observation, interviews, and documentation. The data analysis techniques employed are data reduction, data presentation, conclusion drawing, and verification. The unit of analysis in this research is groups specifically, community groups with a high disaster risk index in Pasaman Regency, such as South Mapat Tunggul Subdistrict, Panti Subdistrict, and Tigo Nagari Subdistrict. The findings reveal that disaster mitigation based on local wisdom in Pasaman Regency has not been optimally implemented. This is evidenced by the lack of proper and comprehensive adoption of local wisdom methods in disaster mitigation activities. For instance, the institutional formation indicator shows that there is no institution beyond the existing organizations involved in this process. Furthermore, the training and education indicators show no visible utilization of the local community's wisdom as a medium for disaster mitigation. However, local wisdom methods that already exist in the community are evident in the early warning system indicator. The community uses natural signs and loudspeakers at places of worship within residential areas as an early warning system. These loudspeakers serve as an information system for the community to conduct self-initiated and independent evacuations.